2020
DOI: 10.1007/s12144-020-01086-4
|View full text |Cite
|
Sign up to set email alerts
|

Rumination, automatic thoughts, dysfunctional attitudes, and thought suppression as transdiagnostic factors in depression and anxiety

Abstract: High comorbidity of anxiety and depression poses challenges to research and treatment in clinical settings. The current study was set out to investigate whether respondents can be separated into discrete depressive and anxious subgroups or reveal a continuous distribution throughout the population based on the symptoms of depression and anxiety. In addition, we also explored the role of rumination, automatic thoughts, dysfunctional attitudes, and thought suppression as transdiagnostic factors. Psychometric ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 146 publications
(153 reference statements)
2
17
0
Order By: Relevance
“… Whitmer and Gotlib (2013) hypothesize that a narrowing of attention in the context of negative affect can lead to a repetitive focus on negative thoughts, thus exacerbating negative mood states. Depressive rumination has been shown to covary with dysfunctional cognitions ( Yapan et al, 2020 ), and interact with dysfunctional cognitions to predict the onset, number, and duration of future depressive episodes ( Robinson and Alloy, 2003 ). In effect, rumination can enhance the harmful impact of negative schemas and cognitions.…”
Section: Psychological Dimensions Relevant To Amotivation and Anhedoniamentioning
confidence: 99%
“… Whitmer and Gotlib (2013) hypothesize that a narrowing of attention in the context of negative affect can lead to a repetitive focus on negative thoughts, thus exacerbating negative mood states. Depressive rumination has been shown to covary with dysfunctional cognitions ( Yapan et al, 2020 ), and interact with dysfunctional cognitions to predict the onset, number, and duration of future depressive episodes ( Robinson and Alloy, 2003 ). In effect, rumination can enhance the harmful impact of negative schemas and cognitions.…”
Section: Psychological Dimensions Relevant To Amotivation and Anhedoniamentioning
confidence: 99%
“…Concerning secondary outcomes, we indicated that NATs and dysfunctional attitudes decreased, whereas unconditional self-acceptance increased, after the CBT intervention, with comparable improvements in both groups. Previous research found that NATs are correlated with depression and anxiety, representing common characteristics among these disorders ( Yapan et al, 2020 ). In concordance with our findings regarding the involvement of NATs in GAD, it was demonstrated that NATs were positively associated with specific symptoms of anxiety disorders ( Iancu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 98%
“…What has also been unexplored is whether this effect of intentionality interacts with taskrelatedness in modulating momentary affect. Based on previous work implicating unintentional thoughts (characterized by lack of control and not requiring any effort) in mentally distressing rumination (Shigemoto et al, 2017) as well as depression and anxiety (Yapan et al, 2020), we predict that we will observe a main effect of intentionality, such that unintentional thoughts will be related to more negative momentary affect than intentional thoughts. Further, given that questionnaire-based research has found a stronger link between affective dysfunction and unintentional compared to intentional task-unrelated thought (Seli et al, 2019), we also hypothesize an interaction between intentionality and taskrelatedness, such that unintentional task-unrelated thought will be more strongly associated with negative affect than intentional task-unrelated thought.…”
Section: Intentionality Of Thought and Its Association With Affective...mentioning
confidence: 93%